(untitled) (Bangladesh Journal of Otorhinolaryngology, 2011)
Dysphagia is the usual presenting feature of oesophageal cancer & is generally a sign of advanced disease. Palliation in this disease demands relief of dysphagia. Palliation of dysphagia can be achieved in a number of ways which includes surgical resection, stenting, laser ablation, photodynamic therapy, ethanol necrosis & bipolar coagulation. We report here a case of dysphagia due to lower oesophageal adenocarcinoma treated by palliative oesophagogestrectomy. Key words: Dysphagia; Adenocarcinoma at oesophagogastric junction; Palliative oesophagogestrectomy. DOI: http://dx.doi.org/10.3329/bjo.v17i2.8859 BJO 2011; 17(2): 150-153